Method for circularly preparing Fe / SiO2 catalyst by utilizing wastes and application of Fe / SiO2 catalyst
By using abandoned green beer bottles to prepare the FE/SIO2 catalyst, combined with optical thermal collaborative technology, the problem of high cost and pollution of traditional catalysts was solved, and high -efficiency and low energy -consuming anti -water transformation reactions were achieved.
Patent Information
- Application Number
- CN202411520292.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-28
AI Technical Summary
Traditional counterwater vapor transformation reaction catalysts have problems such as high cost, pollution, high energy consumption, low selectivity, and low photocatalytic reaction rate, which are difficult to meet the needs of low cost, high efficiency and pollution-free.
By using abandoned green beer bottles to prepare the FE/SIO2 catalyst, combined with optical thermal collaborative technology, light -induced thermal live hydrogen and carbon dioxide can be used to achieve high -efficiency reverse water transformation reactions.
The prepared FE/SIO2 catalyst has high catalytic activity, chemical stability, and good CO yield, reducing the start temperature and activation energy of the reaction, and realizing the reaction of high -efficiency light and thermal water steam transformation.
Smart Images

Figure CN119368179A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of synthesizing carbon monoxide by reverse water vapor shift reaction, and in particular to a method for preparing Fe / SiO2 catalyst by utilizing waste recycling and its application. Background Art
[0002] Among the many ways to convert and utilize carbon dioxide, the reverse water gas shift reaction has attracted attention due to its simple reaction process and the important industrial applications and high economic value of the generated carbon monoxide. However, the reverse water gas shift reaction requires high temperatures and many side reactions, so a suitable catalyst needs to be selected. Traditional catalysts are often only suitable for thermal catalysis or photocatalysis, but these catalysts generally have problems such as easy sintering and deactivation at the high temperatures required for the reaction, large bandgap, and low utilization of natural light. At the same time, traditional reverse water gas shift reaction catalysts are expensive and the production process will inevitably bring pollution. Therefore, there is an urgent need to develop a low-cost, high-efficiency, pollution-free new type of photothermal synergistic reverse water gas shift reaction catalyst.
[0003] The reverse water vapor shift reaction is as follows:
[0004] CO2+H2=CO+H2OΔH=+42.1kJ / mol,
[0005] In the reverse water gas shift reaction, metal nanoparticles are mainly responsible for the activation and dissociation of hydrogen molecules, while oxides serve as substrates to provide the necessary active sites for the adsorption and activation of carbon dioxide. However, traditional catalytic methods, whether thermal or photocatalytic, have shortcomings, such as high energy consumption and low selectivity for thermal catalysis, and low reaction rate for photocatalysis. Combining light energy with thermal energy to form photothermal catalysis can not only efficiently convert carbon dioxide into the target product, but also reduce energy consumption and increase the reaction rate. In the process of synthesizing CO by reverse water gas shift of photothermal catalysis, light energy not only provides thermal energy to activate the adsorbed hydrogen and carbon dioxide, but also excites semiconductors to generate electrons and holes, participating in the activation of the gas. Hydrogen dissociates on metal particles to form hydrogen radicals, which are then transferred to oxygen vacancies to activate carbon dioxide and form carboxyl intermediates. Through further activation, the CO bond breaks, CO is generated and dissociates from the surface, while oxygen vacancies continue to adsorb and activate new carbon dioxide, forming a continuous catalytic cycle.
[0006] Therefore, developing new catalysts to lower the starting temperature of the reaction, increase the CO yield, and reduce the reaction activation energy has become the goal pursued by researchers. Summary of the invention
[0007] One of the purposes of the present invention is to provide a method for preparing Fe / SiO2 catalyst by utilizing waste recycling. The method is simple and can realize the waste recycling of discarded green beer bottles. The prepared Fe / SiO2 catalyst has excellent adsorption strength for carbon dioxide, high catalytic activity under high temperature conditions and good chemical stability. It effectively combines light energy and thermal energy to form photothermal catalysis. The light-induced heat provides sufficient thermal energy to activate the adsorbed hydrogen and carbon dioxide to obtain a high-efficiency photothermal reverse water vapor shift reaction rate.
[0008] The second object of the present invention is to provide a Fe / SiO2 catalyst that effectively combines light energy and thermal energy to form photothermal catalysis. The light-induced heat provides sufficient thermal energy to activate the adsorbed hydrogen and carbon dioxide to obtain an efficient photothermal reverse water vapor shift reaction rate.
[0009] The third object of the present invention is to provide an application of a Fe / SiO2 catalyst prepared by a method for preparing a Fe / SiO2 catalyst by recycling waste.
[0010] The scheme adopted by the present invention to achieve one of the purposes is: a method for preparing Fe / SiO2 catalyst by recycling waste, comprising the following steps:
[0011] S1, mechanically crushing, washing, drying and grinding the discarded green beer bottles into powder in sequence to obtain a silica carrier;
[0012] S2, mixing soluble iron salt and / or ferrous salt with a silica carrier in a dispersant, and calcining the mixture at a certain temperature to obtain a catalyst precursor;
[0013] S3. Reduce the catalyst precursor mixture under a hydrogen atmosphere to obtain a Fe / SiO2 catalyst.
[0014] Preferably, in step S2, the soluble iron salt is at least one of ferric sulfate, ferric chloride, ferric nitrate, and hydrated crystals thereof, and the soluble ferrous salt is at least one of ferrous sulfate, ferrous chloride, and hydrated crystals thereof.
[0015] Preferably, in step S2, the dispersant is any one of anhydrous ethanol, 0.1-1 mol / L sodium hydroxide solution, NH4F aqueous solution, and a mixed solution of trimesic acid and sodium hydroxide.
[0016] Preferably, in step S2, the molar ratio of the soluble iron salt and / or ferrous salt to the silica carrier is 1-50:100.
[0017] Preferably, in step S2, the calcination temperature is 400-800° C., and the calcination time is 1-4 hours.
[0018] In the present invention, the calcination process can convert metal ions into oxides and remove impurities, moisture or some harmful substances, further making the material harder, more resistant to high temperatures or having specific porous properties. An oxidation reaction occurs in the process, which will lay the foundation for the subsequent reduction to nano-sized iron metal in a hydrogen atmosphere.
[0019] Preferably, in step S3, the reduction temperature is 200-800° C., the reduction time is 0.5-5 h, and the flow rate of hydrogen is 10-50 mL / min.
[0020] The present invention aims to provide a method for preparing a Fe / SiO2 catalyst for synthesizing carbon monoxide by an efficient photothermal catalytic reverse water vapor shift reaction and its application, which is prepared by preparing a silica carrier from discarded green beer bottles by a physical grinding and crushing method, loading ferric nitrate on the silica carrier, and reducing a catalyst precursor. The silica carrier increases the adsorption strength of the catalyst to carbon dioxide, which is beneficial to improving the reaction activity of the reverse water vapor shift reaction. In addition, the carrier can play a good dispersing role on iron metal. At the same time, iron nanoparticles have high catalytic activity and good chemical stability under high temperature conditions, which increases the yield of carbon monoxide and ultimately reduces the Ea of the entire reaction. In addition, light energy and heat energy are effectively combined to form photothermal catalysis, and light-induced heat provides sufficient heat energy to activate the adsorbed hydrogen and carbon dioxide to obtain an efficient photothermal reverse water vapor shift reaction rate.
[0021] The solution adopted by the present invention to achieve the second purpose is: an Fe / SiO2 catalyst is prepared by the method described.
[0022] The solution adopted by the present invention to achieve the third purpose is: an application of the Fe / SiO2 catalyst prepared by the method described above, and applying the Fe / SiO2 catalyst to the photothermal catalytic reverse water vapor shift reaction to synthesize carbon monoxide.
[0023] The present invention has the following advantages and beneficial effects:
[0024] The present invention uses discarded green beer bottles whose main component is silicon dioxide as a carrier, and can realize waste recycling. The silicon dioxide carrier increases the adsorption strength of the catalyst to carbon dioxide, which is beneficial to improving the reaction activity of the reverse water vapor shift reaction. In addition, the carrier can play a good dispersing role on iron metal. At the same time, iron nanoparticles have high catalytic activity and good chemical stability under high temperature conditions, which increases the yield of carbon monoxide and ultimately reduces the Ea of the entire reaction. In addition, light energy and heat energy are effectively combined to form photothermal catalysis, and light-induced heat provides sufficient heat energy to activate the adsorbed hydrogen and carbon dioxide to obtain an efficient photothermal reverse water vapor shift reaction rate. The preparation process of the present invention is easy to control, the method is simple, and it is easy to promote and apply industrialization.
[0025] The silica carrier prepared by using discarded green beer bottles as raw materials in the present invention has higher catalytic efficiency and good regeneration performance than the Fe / SiO2 catalyst prepared by the traditional pure silica carrier. At the same time, the raw material is discarded green beer bottles, which realizes waste utilization and effectively avoids the harm to the environment caused by a large amount of glass waste every year. Considering its good catalytic effect and low cost, it has high feasibility in actual industrial applications and has good economic value and application promotion prospects.
[0026] The invention is suitable for preparing a catalyst for synthesizing carbon monoxide by reverse water-gas shift reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a 200nm scanning electron microscope image of a silica carrier obtained by grinding and crushing commonly used discarded green beer bottles on the market in a specific embodiment;
[0028] Figure 2 This is a 500nm scanning electron microscope image of the 10% Fe@SiO2 catalyst particles in Example 2;
[0029] Figure 3 XRD patterns of the 10% Fe@SiO2 catalyst prepared in Example 2 and pure waste green beer bottles;
[0030] Figure 4 100mg 10% Fe@SiO2 catalyst sample was heated at 300-550℃, 100mW / cm 2 XRD patterns of the catalyst before and after 5h of catalytic reverse water gas shift reaction under light conditions;
[0031] Figure 5 10% Fe@SiO2 catalyst sample and its heating at 300-550℃, 100mW / cm 2 XRD pattern of the catalytic reverse water gas shift reaction after 5h of regeneration under light conditions;
[0032] Figure 6 100mg 10% Fe@SiO2 catalyst sample was heated at 300-550℃, 100mW / cm 2 The CO production rate and selectivity obtained by catalyzing the reverse water gas shift reaction for 5 h under light conditions;
[0033] Figure 7 100 mg Fe@SiO2 catalyst samples with different loadings (5%, 10%, 15%, 20%) were heated at 300-550℃ and 100 mW / cm 2 The CO2 conversion rate diagram obtained by catalyzing the reverse water gas shift reaction for 5 h under light conditions;
[0034] Figure 8 10% Fe@SiO2 catalyst heated at 300-550℃, 100mW / cm 2 The reverse water-gas shift reaction was catalyzed for 5 hours under light conditions and then regenerated three times and heated at 300-550℃ and 100mW / cm 2 The CO2 conversion rate diagram obtained by catalyzing the reverse water gas shift reaction for 5 h under light conditions;
[0035] Fig. 9 This is a graph of CO2 conversion obtained by catalyzing the reverse water gas shift reaction of 10% Fe@SiO2 catalyst at 300-550℃ with or without light for 5h. DETAILED DESCRIPTION
[0036] For a better understanding of the present invention, the following examples are provided to further illustrate the present invention, but the present invention is not limited to the following examples.
[0037] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.
[0038] Example 1
[0039] Preparation method of 5% Fe@SiO2 catalyst
[0040] A method for preparing Fe / SiO2 catalyst by recycling waste, comprising the following steps:
[0041] (S1) Preparation of silica carrier by physical grinding and crushing method:
[0042] Common discarded green beer bottles on the market were mechanically crushed, 10 g of which was added to 100 mL of deionized water, stirred and allowed to stand for 3 min at room temperature, and the upper turbid liquid was removed by decantation. The above steps were repeated 5 times to remove dust and impurities attached to the surface of the raw material;
[0043] The cleaned small pieces of raw materials were transferred to an oven for drying at a temperature of 80°C for 2 hours to obtain a solid substance, which was then ground into a solid powder using a mortar to obtain a silica carrier;
[0044] (S2) Silica carrier loaded with iron nitrate:
[0045] Weigh 3.37 g of ferric nitrate nonahydrate crystals, and mix the ferric nitrate nonahydrate crystals with a silica carrier;
[0046] Transfer the ferric nitrate nonahydrate and silicon dioxide mixture into a mortar, add 5 mL of anhydrous ethanol and stir continuously to disperse and mix the ferric nitrate nonahydrate evenly;
[0047] The mixture was placed in a muffle furnace and calcined at 500° C. for 2 h to obtain a mixture of ferric oxide, ferrous oxide and ferrosoferric oxide supported on silica;
[0048] (S3) Catalyst Precursor Reduction
[0049] The catalyst precursor mixture was loaded into a reactor and reduced at 350° C. in a hydrogen atmosphere for 2 h to obtain a 5% Fe@SiO2 catalyst.
[0050] Example 2
[0051] Preparation method of 10% Fe@SiO2 catalyst
[0052] A method for preparing Fe / SiO2 catalyst by recycling waste, comprising the following steps:
[0053] (S1) Preparation of silica carrier by physical grinding and crushing method:
[0054] Common discarded green beer bottles on the market were mechanically crushed, 10 g of which was added to 100 mL of deionized water, stirred and allowed to stand for 3 min at room temperature, and the upper turbid liquid was removed by decantation. The above steps were repeated 5 times to remove dust and impurities attached to the surface of the raw material;
[0055] The cleaned small pieces of raw materials were transferred to an oven for drying at a temperature of 80°C for 2 hours to obtain a solid substance, which was then ground into a solid powder using a mortar to obtain a silica carrier;
[0056] (S2) Silica carrier loaded with iron nitrate:
[0057] Weigh 6.73 g of ferric nitrate nonahydrate crystals, and mix the ferric nitrate nonahydrate crystals with a silica carrier;
[0058] Transfer the ferric nitrate nonahydrate and silicon dioxide mixture into a mortar, add 5 mL of anhydrous ethanol and stir continuously to disperse and mix the ferric nitrate nonahydrate evenly;
[0059] The mixture was placed in a muffle furnace and calcined at 500° C. for 2 h to obtain a mixture of ferric oxide, ferrous oxide and ferrosoferric oxide supported on silica;
[0060] (S3) Catalyst precursor reduction:
[0061] The catalyst precursor mixture was loaded into a reactor and reduced at 350° C. in a hydrogen atmosphere for 2 h to obtain a 10% Fe@SiO 2 catalyst.
[0062] Example 3
[0063] Preparation method of 15% Fe@SiO2 catalyst
[0064] A method for preparing Fe / SiO2 catalyst by recycling waste, comprising the following steps:
[0065] (S1) Preparation of silica carrier by physical grinding and crushing method:
[0066] Common discarded green beer bottles on the market were mechanically crushed, 10 g of which was added to 100 mL of deionized water, stirred and allowed to stand for 3 min at room temperature, and the upper turbid liquid was removed by decantation. The above steps were repeated 5 times to remove dust and impurities attached to the surface of the raw material;
[0067] The cleaned small pieces of raw materials were transferred to an oven for drying at a temperature of 80°C for 2 hours to obtain a solid substance, which was then ground into a solid powder using a mortar to obtain a silica carrier;
[0068] (S2) Silica carrier loaded with iron nitrate:
[0069] Weigh 10.10 g of ferric nitrate nonahydrate crystals, and mix the ferric nitrate nonahydrate crystals with a silica carrier;
[0070] Transfer the ferric nitrate nonahydrate and silicon dioxide mixture into a mortar, add 5 mL of anhydrous ethanol and stir continuously to disperse and mix the ferric nitrate nonahydrate evenly;
[0071] The mixture was placed in a muffle furnace and calcined at 500° C. for 2 h to obtain a mixture of ferric oxide, ferrous oxide and ferrosoferric oxide supported on silica;
[0072] (S3) Catalyst precursor reduction:
[0073] The catalyst precursor mixture was loaded into a reactor and reduced at 350° C. in a hydrogen atmosphere for 2 h to obtain a 15% Fe@SiO2 catalyst.
[0074] Example 4
[0075] Preparation method of 20% Fe@SiO2 catalyst
[0076] A method for preparing Fe / SiO2 catalyst by recycling waste, comprising the following steps:
[0077] (S1) Preparation of silica carrier by physical grinding and crushing method:
[0078] Common discarded green beer bottles on the market were mechanically crushed, 10 g of which was added to 100 mL of deionized water, stirred and allowed to stand for 3 min at room temperature, and the upper turbid liquid was removed by decantation. The above steps were repeated 5 times to remove dust and impurities attached to the surface of the raw material;
[0079] The cleaned small pieces of raw materials were transferred to an oven for drying at a temperature of 80°C for 2 hours to obtain a solid substance, which was then ground into a solid powder using a mortar to obtain a silica carrier;
[0080] (S2) Silica carrier loaded with iron nitrate:
[0081] Weigh 13.47 g of ferric nitrate nonahydrate crystals, and mix the ferric nitrate nonahydrate crystals with a silica carrier;
[0082] Transfer the ferric nitrate nonahydrate and silicon dioxide mixture into a mortar, add 5 mL of anhydrous ethanol and stir continuously to disperse and mix the ferric nitrate nonahydrate evenly;
[0083] The mixture was placed in a muffle furnace and calcined at 500° C. for 2 h to obtain a mixture of ferric oxide, ferrous oxide and ferrosoferric oxide supported on silica;
[0084] (S3) Catalyst precursor reduction:
[0085] The catalyst precursor mixture was loaded into a reactor and reduced at 350° C. in a hydrogen atmosphere for 2 h to obtain a 20% Fe@SiO2 catalyst.
[0086] Comparative Example 1
[0087] The difference between this comparative example and Examples 1-4 is that the discarded green beer bottles are replaced with silicon dioxide, and 5% Fe@SiO2 catalyst (silicon dioxide), 10% Fe@SiO2 catalyst (silicon dioxide), 15% Fe@SiO2 catalyst (silicon dioxide), and 20% Fe@SiO2 catalyst (silicon dioxide) are prepared respectively.
[0088] Catalyst characterization
[0089] Figure 1 This is a 200nm electron microscope image of the silica carrier obtained from the commonly used discarded green beer bottles in the embodiments of the present invention. From the electron microscope image, it can be seen that the silica carrier particles are irregular in shape, with a relatively smooth surface and a certain layered structure. This appearance is related to the microscopic lattice structure of the silica itself.
[0090] Figure 2 This is a 500nm scanning electron microscope image of the 10% Fe@SiO2 catalyst particles in Example 2; it can be seen from the electron microscope image that the appearance of the catalyst particles has changed significantly after the iron is loaded. The dot-like distribution of the fluffy part on the silica carrier in the figure is the loaded nano-iron particles. The nano-iron particles are distributed more evenly on the load and have good adsorption. The silica carrier is still irregular after loading, indicating that the loading process has little effect on the carrier.
[0091] Figure 3 This is the XRD diagram of the 10% Fe@SiO2 catalyst prepared in Example 2 and pure discarded green beer bottles; the figure shows the characteristic peak of Fe2O3 after loading, indicating that the iron element in the catalyst mainly exists in the form of trivalent iron.
[0092] Figure 4 100mg 10% Fe@SiO2 catalyst sample was heated at 300-5500℃, 100mW / cm 2 XRD patterns of the catalyst before and after 5h of reverse water gas shift reaction under light irradiation; it can be seen that the XRD characteristic peaks are Figure 3 There is a big change compared with the above, indicating that the catalyst has been significantly modified after a period of reaction. The figure also shows the impurity peak of carbon element, indicating that there is carbon deposition on the surface of the catalyst after the reaction.
[0093] Figure 5 10% Fe@SiO2 catalyst sample and its heating at 300-550℃, 100mW / cm 2 XRD diagram after regeneration after catalytic reverse water gas shift reaction under light conditions for 5 hours; it can be seen that the characteristic peak of carbon element disappears and the characteristic peak of Fe3O4 appears, indicating that the iron element in the catalyst after regeneration mainly exists in the form of Fe3O4.
[0094] Catalyst evaluation
[0095] After sieving and dispersing, 100 mg of 10% Fe@SiO2 catalyst sample was loaded into the photothermal reaction tube, and the reaction tube was placed in a muffle furnace and 100 mW / cm 2 White light illumination. CO2 and H2 were introduced as reaction gases in a ratio of 1:4, N2 was used as carrier gas, H2 flow rate was 12mL / min, and pressure was normal pressure. The reaction temperature was adjusted from 300℃ to 550℃ to obtain Figure 6 The experimental results are shown in Figure 2. The experimental results show that the CO selectivity is almost 100% under the action of the catalyst, and the reaction rate reaches the maximum value at 500°C.
[0096] Take catalyst samples with different loading amounts and repeat the above experimental process to obtain Figure 7 It can be seen that within the range of 5%-20% loading, the greater the loading, the better the catalytic performance of the catalyst at 500°C. However, when the temperature continues to rise, the catalytic efficiency of the catalyst with high loading decreases, which is related to the sintering and carbon deposition of the catalyst caused by the high temperature during the reaction. Figure 4 This can be proved by the XRD pattern after the reaction.
[0097] The 10% Fe@SiO2 catalyst was heated at 300-550°C and 100 mW / cm 2The catalytic reverse water gas shift reaction was carried out under light conditions for 5 hours and then regenerated three times. The regeneration conditions were sintering at 600 ° C for 5 hours and heating at 300-550 ° C and 100 mW / cm 2 The CO2 conversion rate was obtained by catalyzing the reverse water gas shift reaction for 5 hours under light conditions. Figure 8 As shown in the figure, it can be seen that the performance of the catalyst has decreased after regeneration, but the decrease is not obvious. In the long-term reaction test, it still shows excellent catalytic performance. The actual test shows that the catalyst has good regeneration performance.
[0098] Fig. 9 The CO2 conversion rate diagram of 10% Fe@SiO2 catalyst catalyzed the reverse water vapor shift reaction for 5 hours under heating at 300-550℃ with or without light. It can be seen from the figure that within the temperature range taken in the experiment, under most temperature conditions, light has shown a promoting effect on the reverse water vapor shift reaction, which shows the excellent light-heat synergy of the catalyst of the present invention. However, the reaction rate of the light group at 550℃ is slightly lower than that of the lightless group, which is related to the more complex reaction mechanism and the difference in dominant conditions.
[0099] Table 1 shows the data of the catalytic performance of the catalysts prepared in Examples 1-4 and Comparative Example 1, pure waste green beer bottles, and silicon dioxide:
[0100] Table 1
[0101]
[0102]
[0103] It can be seen from the data in Table 1 that the Fe@SiO2 catalyst of the present invention, which uses discarded green beer bottles as the source of the silica substrate, has a higher catalytic performance, i.e., a catalytic CO2 conversion rate, than the Fe@SiO2 catalyst with an ordinary SiO2 substrate at most temperatures under the premise of the same iron loading.
[0104] The silica carrier prepared by using discarded green beer bottles as raw materials in the present invention has higher catalytic efficiency and good regeneration performance than the Fe / SiO2 catalyst prepared by the traditional pure silica carrier. At the same time, the raw material is discarded green beer bottles, which realizes waste utilization and effectively avoids the harm to the environment caused by a large amount of glass waste every year. Considering its good catalytic effect and low cost, it has high feasibility in actual industrial applications and has good economic value and application promotion prospects.
[0105] The invention is suitable for preparing a catalyst for synthesizing carbon monoxide by reverse water-gas shift reaction.
[0106] The above is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and changes can be made without departing from the principle of the present invention, and these improvements and changes are also regarded as the protection scope of the present invention.
Claims
1. A method for preparing Fe / SiO2 catalyst by recycling waste, characterized in that: The following steps are involved: S1, mechanically crushing, washing, drying and grinding discarded green beer bottles into powder in sequence to obtain a silica carrier; S2, mixing soluble iron salt and / or ferrous salt with a silica carrier in a dispersant, and calcining the mixture at a certain temperature to obtain a catalyst precursor; S3. Reduce the catalyst precursor mixture under a hydrogen atmosphere to obtain a Fe / SiO2 catalyst.
2. The method for preparing Fe / SiO2 catalyst by recycling waste according to claim 1, characterized in that: In step S2, the soluble iron salt is at least one of ferric sulfate, ferric chloride, ferric nitrate, and hydrated crystals thereof, and the soluble ferrous salt is at least one of ferrous sulfate, ferrous chloride, and hydrated crystals thereof.
3. The method for preparing Fe / SiO2 catalyst by recycling waste according to claim 1, characterized in that: In the step S2, the dispersant is any one of anhydrous ethanol, 0.1-1 mol / L sodium hydroxide solution, NH4F aqueous solution, and a mixed solution of trimesic acid and sodium hydroxide.
4. The method for preparing Fe / SiO2 catalyst by recycling waste according to claim 1, characterized in that: In the step S2, the molar ratio of the soluble iron salt and / or ferrous salt to the silica carrier is 1-50:
100.
5. The method for preparing Fe / SiO2 catalyst by recycling waste according to claim 1, characterized in that: In the step S2, the calcination temperature is 400-800° C. and the calcination time is 1-4 hours.
6. The method for preparing Fe / SiO2 catalyst by recycling waste according to claim 1, characterized in that: In the step S3, the reduction temperature is 200-800° C., the reduction time is 0.5-5 h, and the flow rate of hydrogen is 10-50 mL / min.
7. A Fe / SiO2 catalyst, characterized in that: The method according to any one of claims 1 to 6 is adopted to prepare the present invention.
8. Use of a Fe / SiO2 catalyst prepared by the method according to any one of claims 1 to 6, characterized in that: The Fe / SiO2 catalyst is applied to synthesize carbon monoxide through photothermal catalytic reverse water gas shift reaction.